Mars and Venus in Action? The US and EU’s foreign relations strategies in academic discourse - Giedraityte, Ieva (Baltic Journal of Political Science, 2018)
[full article and abstract in English]This article reviews the existing academic literature that compares and explains the differences between the US and the EU’s external actions. An analytical matrix is devised to group publications by level of analysis (micro-, mid-, and macro) and by theme of comparison criteria. The key findings are that in the macro level of analysis, authors tend to compare the role actors have in international relations before claiming either that the EU is a different kind of power due to its peculiar historical experience, or that the EU is weak due to its complicated structure and lack of military capacities. Furthermore, authors conducting their analyses at the micro level tend to find more similarities between the EU and the US’s external actions than those working at the macro level. The article concludes by making a point in favour of further comparisons as an essential tool to better understand the EU and other actors in international relations.
Keywords: EU; US; actorness; regionalism; security studies; democratization studies